Kecemasan Dasar Tokoh Utama dalam Novel al-Lish wa al-Kilab: Kecemasan Dasar Tokoh Utama dalam Novel al-Lish wa al-Kilab - Sandra, Bella; Choironi, Merry; Rahmawati, Isnaini (Kitabina: Jurnal Bahasa dan Sastra, 2023)
This study aims to describe the factors that make up basic anxiety and the main character's actions in overcoming basic anxiety in the novel Al-Lish Wa Al Kilab based on Karen Horney's theory. This study used descriptive qualitative method. The technique used is the reading and note technique. The results of this study are the factors that form basic anxiety, namely interpersonal conflict factors in the form of non-fulfillment of Karen Horney's neurotic needs including affection and acceptance needs, partner needs, life limiting needs, ambition and achievement needs, social recognition needs, the need to be an admired person, need for power, need for independence, and need for perfection. Intrapsychic factors in the form of ideal self-image and self-loathing, the main character fulfills all self-images, namely the search for neurotic grandeur, neurotic claimants, neurotic pride and fulfills all forms of expression of self-loathing, namely self-deprecation, self-blame, self-demanding without measure, self-frustration, self-torture and self-destruct. The action in overcoming basic anxiety is that the main character uses all means, namely approaching, moving away, and fighting other people. the most dominant action taken is against other people.